ANALISIS BEBERAPA FAKTOR YANG BERPENGARUH TERHADAP PROSES PENGEMBANGAN KUALITAS SISTEM - Amrul, Sadat (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2005)
This research test directly factors influencing for systems development quality, like: user participation, user training, user expertise, user /developer communication, user Influence, and user conflict. Persuant to answer 86 respondent employee banking industry in Banjarmasin. Result of examination of partial regretion indicate that user training and user/developer communication have an effect on positive and significant to systems developmentÂ quality, while user participation, user influence, user expertise and user conflict not have an effect on by partial to systems development quality.Â